2017
DOI: 10.1016/j.drugalcdep.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Trends and correlates of marijuana use among late middle-aged and older adults in the United States, 2002–2014

Abstract: Background Recent trend studies suggest that marijuana use is on the rise among the general population of adults ages 18 and older in the United States. However, little is known about the trends in marijuana use and marijuana-specific risk/protective factors among American adults during the latter part of adulthood. Method Findings are based on repeated, cross-sectional data collected from late middle-aged (ages 50–64) and older adults (ages 65 and older) surveyed as part of the National Survey on Drug Use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 21 publications
5
81
1
1
Order By: Relevance
“…Self‐reported cannabis use among respondents in our study was 24% within the last year and 21% within the last month. These levels are more than double those reported in national prevalence studies, where rates vary between 1.8% and 8.3% over 1 month and between 2.8% and 12.9% over 1 year . The younger demographic drives rates in most large studies, in which nearly 20% of 18‐ to 25‐year‐olds are reported to use cannabis .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Self‐reported cannabis use among respondents in our study was 24% within the last year and 21% within the last month. These levels are more than double those reported in national prevalence studies, where rates vary between 1.8% and 8.3% over 1 month and between 2.8% and 12.9% over 1 year . The younger demographic drives rates in most large studies, in which nearly 20% of 18‐ to 25‐year‐olds are reported to use cannabis .…”
Section: Discussionmentioning
confidence: 83%
“…These levels are more than double those reported in national prevalence studies, where rates vary between 1.8% and 8.3% over 1 month and between 2.8% and 12.9% over 1 year. [2][3][4][21][22][23][24][25] The younger demographic drives rates in most large studies, in which nearly 20% of 18-to 25-year-olds are reported to use cannabis. 2 In contrast, those under the age of 30 years made up only 6% of our total respondents but had rates of active use of nearly 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly one‐quarter of current users were aged 85 and older, and many had a high level of education. These data are contrary to other previously published studies in which individual marijuana users tended to be male, black, and less educated …”
Section: Discussionmentioning
confidence: 99%
“…After alcohol and tobacco, marijuana is the most commonly used psychoactive substance in the United States (1). Recent epidemiological data show that marijuana use has increased significantly over the past decade among all demographic subgroups, with especially notable increases among middle-aged and older adults (2)(3)(4). A study based on the 2012-2013 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC-III) found that 3.9% of the 50+ age group reported past-year marijuana use (5).…”
Section: Introductionmentioning
confidence: 99%